Real-world data on induction therapy in patients with transplant-ineligible newly diagnosed multiple myeloma: retrospective analysis of 598 cases from Kansai Myeloma Forum - Shimura, Yuji; Shibayama, Hirohiko; Nakaya, Aya; Yamamura, Ryosuke; Imada, Kazunori; Kaneko, Hitomi; Hanamoto, Hitoshi; Fuchida, Shin-ichi; Tanaka, Hirokazu; Kosugi, Satoru; Kiyota, Miki; Matsui, Toshimitsu; et al. (International journal of hematology, 2023)
To investigate the real-world clinical outcomes and management of novel drug-containing therapies for newly diagnosed multiple myeloma (MM) patients, we retrospectively analyzed data on the first-line treatment for newly diagnosed transplant-ineligible MM patients from Kansai Myeloma Forum, a registry network in Japan. A total of 598 patients treated with novel drugs between March 2007 and February 2018 were analyzed. Regimens used were VD ( n = 305), Rd ( n = 103), VMP ( n = 97), VCD ( n = 71), and VRd ( n = 22). Younger patients tended to receive VRd or VCD, whereas the regimen with the highest median patient age was Rd. More than three-quarters of patients in the Rd group received a reduced dose of lenalidomide. The Rd and VRd groups had a relatively high incidence of infection and skin complications, and the VMP group had the highest incidence of peripheral neuropathy. Overall response rate did not differ significantly between regimens. Multivariate analysis in all patients revealed several poor prognostic factors, such as poor performance status. Novel drug-containing regimens for newly diagnosed MM showed a durable response with manageable AEs in the real-world setting.